2022
DOI: 10.1177/17588359211058393
|View full text |Cite
|
Sign up to set email alerts
|

Adverse events induced by nivolumab and ipilimumab combination regimens

Abstract: Background: No meta-analysis has assessed the pooled frequencies of adverse events (AEs) induced by concomitant nivolumab plus ipilimumab regimen for anticancer-medications-naïve malignancies. Furthermore, no meta-analysis has compared detailed safety profiles between four doses of nivolumab 3 mg/kg plus ipilimumab 1 mg/kg every 3 weeks (N3I1) and four doses of nivolumab 1 mg/kg plus ipilimumab 3 mg/kg every 3 weeks (N1I3). Objectives of this study was estimating AE frequencies, and comparison of AE frequencie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 29 publications
0
12
0
Order By: Relevance
“…This may be because MPM is a low tumor mutational burden (TMB) tumor ( 63 ). In addition, approximately 40% of patients treated with nivolumab plus ipilimumab experienced grade 3 or higher adverse events (AEs) ( 64 ).…”
Section: Discussionmentioning
confidence: 99%
“…This may be because MPM is a low tumor mutational burden (TMB) tumor ( 63 ). In addition, approximately 40% of patients treated with nivolumab plus ipilimumab experienced grade 3 or higher adverse events (AEs) ( 64 ).…”
Section: Discussionmentioning
confidence: 99%
“…In the CheckMate-142 study of ipilimumab and nivolumab, Grade 3 and 4 irAEs were observed in 32% and 13% of patients, respectively, and these led to treatment discontinuation. In a random-model meta-analysis representing 4677 patients that received nivolumab–ipilimumab regimens [ 52 ], an estimated 40.6% of patients (95% CI 35.7–45.5) experienced a grade 3 or higher adverse event, and an estimated 28.3% of patients (95% CI 23.7–32.8) discontinued their treatment due to adverse events. Common adverse events include fatigue (27.9%, CI 22.6–33.3), pruritus (24.6%, CI 20.3–28.8), rash (24.0%, CI 19.3–28.7), elevated aspartate aminotransferase (21.2%, CI 14.9–27.5), and elevated alanine aminotransferase (18.1%, CI 13.1–23.2).…”
Section: Ici Toxicity Managementmentioning
confidence: 99%
“…Besides, our analyses revealed safety superiority of the N3I1 regimen ( Fig. 1 ) [ 3 ]. The data from Tawbi et al.…”
mentioning
confidence: 99%
“…To compare the risk of adverse events caused by these two regimes, we have recently conducted a random-model meta-analysis using a generic inverse variance method and the data of patients with both melanoma and the other malignancies (RevMan ver 5.4. Cochrane Collaboration, London, UK) [ 3 ]. This analysis suggested that N3I1 regimen caused less adverse events [ 3 ].…”
mentioning
confidence: 99%
See 1 more Smart Citation